EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN PROBLEM BASED LEARNING (PBL) PADA PRESTASI BELAJAR MATEMATIKA DITINJAU DARI MULTIPLE INTELLIGENCES SISWA SMP KABUPATEN LAMPUNG TIMUR TAHUN PELAJARAN 2012/2013 - Hariyati, Endang; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of the research were to determine the effect of learning models on learning achievement viewed from studentsâ multiple intelligences. The learning models compared were cooperative learning model Teams Assisted Individualization (TAI), Problem Based Learning (PBL) and conventional. This research was a quasi-experimental research using Â factorial design. The populations of the research were all students of Junior High School (SMP) on Lampung Timur Regency. The samples of the research were the eight grade students of SMP Negeri 1 Pekalongan, SMP Negeri 2 Pekalongan, and SMP Negeri 3 Batanghari containing 282 students (94 students for first experimental class, 93 students for second experimental class, and 95 students for control class). The samples were chosen by using stratified cluster random sampling. In collecting the data, the instruments used were test and questionnaire. Test was used to get the studentsâ learning achievement data and questionnaire was used to get multiple intelligences data. The technique of analyzing the data was unbalanced two-ways Anova. The result of the research are as follows Â (1) Cooperative learning model TAI provides better mathematics achievement thanÂ the conventional model of learning and PBL, PBL learning model produces better performance over the conventional learning. (2) Multiple intelligences with mathematics logic types provide better math achievement than other types of multiple intelligences linguistic and interpersonal, the type of multiple intelligences linguistic providing academic achievement as well as the type of multiple intelligences interpersonal. (3) The students with LI multiple intelligences type, cooperative learning model TAI has the same mathematics achievement with the PBL model, PBL model has better performance than conventional models, and cooperative learning model TAI has the same mathematics achievement with conventional learning models. The students with multiple intelligences mathematics logic type, TAI cooperative learning model provides a better learning achievement than learning model PBL, PBL learning model provides academic achievement as well as conventional learning models, cooperative learning model TAI provide significantly better learning achievement than with conventional learning models. The students with multiple intelligences type interpersonal, TAI cooperative learning model, PBL and conventional provide similar good performance. (4) The students use cooperative learning model TAI, the type of multiple intelligences linguistic provide better learning achievement than the interpersonal category of multiple intelligences, linguistic multiple intelligences category provides academic achievement as well as multiple intelligences mathematics logic category, the category of multiple intelligences significantly provide that mathematic logic achievement as well as multiple intelligences interpersonal category. The students use PBL and conventional learning models, the type of linguistic multiple intelligences, the mathematics logic type of multiple intelligences and type the interpersonal produces similar good performance. Keywords: TAI, PBL, multiple intelligences Â